2023
DOI: 10.3390/cells12091228
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Omic Analysis Delineates Pathways Modulating Toxic TDP-43 Protein Aggregates in Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a multi-systemic, incurable, amyloid disease affecting the motor neurons, resulting in the death of patients. The disease is either sporadic or familial with SOD1, C9orf72, FUS, and TDP-43 constituting the majority of familial ALS. Multi-omics studies on patients and model systems like mice and yeast have helped in understanding the association of various signaling and metabolic pathways with the disease. The yeast model system has played a pivotal role in elucidating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“… 65 , 66 Recent studies showed that the deregulated metabolism of glycerolipid was associated with ALS risk. 67 , 68 Given that the A allele of rs28610182 had a protective effect (shown in Supplementary Table 6 ) and was associated with upregulated TMEM68 expression in human brain (shown in Supplementary Table 12 ), our findings may indicate a protective influence of this protein product and/or the glycerolipid metabolism pathway, in LATE‐NC.…”
Section: Discussionmentioning
confidence: 80%
“… 65 , 66 Recent studies showed that the deregulated metabolism of glycerolipid was associated with ALS risk. 67 , 68 Given that the A allele of rs28610182 had a protective effect (shown in Supplementary Table 6 ) and was associated with upregulated TMEM68 expression in human brain (shown in Supplementary Table 12 ), our findings may indicate a protective influence of this protein product and/or the glycerolipid metabolism pathway, in LATE‐NC.…”
Section: Discussionmentioning
confidence: 80%
“…Integrated transcriptomic and metabolomic analysis is the most recently developed and promising methodological approach that uses yeast as a model system to understand the biological role of the described proteins in the deregulation of pathways associated with the disease. To date, only preliminary, but encouraging, results have been obtained, and in our view, further research is warranted [139,140].…”
Section: Tdp-4 Fus and Sod1mentioning
confidence: 88%
“…Alzheimer's disease (AD), Parkinson's disease, and Huntington's disease (HD) are among the neurodegenerative diseases associated with protein aggregation and lead to cognitive, behavioral, and motor dysfunction. 1–5 A study conducted by the WHO estimated that over thirty seven million individuals around the world are terribly affected by AD 6 and that the number will reach 66 million by 2030 and 115 million by 2050. 7 The disease is clinically identified by amnestic cognitive impairment, learning disability, memory loss, and a wide array of neuropsychiatric signs during midlife and late life, which indicate that this disease affects the ability to think and perform daily activities independently.…”
Section: Introductionmentioning
confidence: 99%